CONTEXTUAL TEACHING & LEARNING-ORIENTED STUDENT WORKSHEET TO IMPROVE SCIENCE LITERACY ON CHEMISTRY EQUILIBRIUM MATERIALS - Ilmiatul Mufa’idah; Utiya Azizah (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2024)
The challenges of 21st century skills are in line with the objectives of the Merdeka Curriculum, one of which is to grow the ability to analyse various scientific issues and evaluate various phenomena in everyday life. The purpose of this study is to produce contextual teaching and learning-oriented student worksheets that can improve science literacy skills on chemical equilibrium material. The method used in this research refers to the Borg and Gall development model, but is limited to the product trial stage. This research design uses One Group Pretest Post-test. The feasibility of the student worksheet related to the validity aspect is measured based on the results of the assessment of 3 validators, the practicality aspect is reviewed from the results of the response questionnaire and observation of student activities, while the effectiveness aspect is seen from the N-gain value of the pretest - post-test of science literacy. The results of this study showed that the content validity was 87.88% and construct validity was 90.79% with a very valid category, the practicality value was 96.1% positive response and 94.43% based on student activity, and the average N-gain was 0.8853 in the high category. In conclusion, the contextual teaching and learning oriented student worksheet is valid, practical, and effective to improve students' science literacy on chemical equilibrium material.